Gender, Steroids, and Fairness in Sport - John William Devine (Sport, Ethics and Philosophy, 2019)
Eligibility to compete in sport is organised principally around two binary distinctions: ‘clean/doped’ and ‘male/female’. These distinctions are challenged both by steroid users who wish to return to competition following a period of suspension, and trans women athletes who wish to compete in women’s events. Recent empirical work has suggested that steroid users retain an elevated capacity for muscle reacquisition years after they cease to use steroids. I suggest that an analogous worry may arise with respect to certain trans women athletes who wish to compete in women’s events. If sound, this argument would establish an unexpected parallel between eligibility debates surrounding returning dopers and trans women athletes.